2010
DOI: 10.1007/978-3-642-15334-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of C–C Bonds via Iridium-Catalyzed Hydrogenation and Transfer Hydrogenation

Abstract: The formation of C-C bonds via catalytic hydrogenation and transfer hydrogenation enables carbonyl and imine addition in the absence of stoichiometric organometallic reagents. In this review, iridium-catalyzed C-C bond-forming hydrogenations and transfer hydrogenations are surveyed. These processes encompass selective, atom-economic methods for the vinylation and allylation of carbonyl compounds and imines. Notably, under transfer hydrogenation conditions, alcohol dehydrogenation drives reductive generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 134 publications
(33 citation statements)
references
References 293 publications
(139 reference statements)
1
32
0
Order By: Relevance
“…This quality is embodied by alkene hydroformylation, the prototypical carbon-carbon bond–forming hydrogenation and largest-volume application of homogenous catalysis (5, 6). Accordingly, systematic efforts toward the discovery and development of carbon-carbon bond–forming hydrogenations were initiated in our laboratory (7, 8). We have found that diverse π-unsaturated reactants reductively couple to carbonyl compounds and imines under hydrogenation conditions or transfer hydrogenation conditions employing a sacrificial reductant (such as isopropanol), offering an alternative to the use of stoichiometric organometallic reagents.…”
mentioning
confidence: 99%
“…This quality is embodied by alkene hydroformylation, the prototypical carbon-carbon bond–forming hydrogenation and largest-volume application of homogenous catalysis (5, 6). Accordingly, systematic efforts toward the discovery and development of carbon-carbon bond–forming hydrogenations were initiated in our laboratory (7, 8). We have found that diverse π-unsaturated reactants reductively couple to carbonyl compounds and imines under hydrogenation conditions or transfer hydrogenation conditions employing a sacrificial reductant (such as isopropanol), offering an alternative to the use of stoichiometric organometallic reagents.…”
mentioning
confidence: 99%
“…Titanocene-catalyzed silane-mediated reductive cyclizations of 1,5-enones and enals were reported by Buchwald (5,6) and Crowe (7) in 1995; however, intermolecular variants remain elusive. The concept of transfer hydrogenative carbonyl addition introduced by our laboratory (8-10) provides an important inroad to this problem. Using ruthenium(0) catalysts, vicinally oxygenated secondary alcohols serve dually as reductants and carbonyl precursors (11, 12) (Figure 2).…”
Section: α-Olefins and Styrenesmentioning
confidence: 99%
“…25,26 As documented in this account, ruthenium catalyzed transfer hydrogenation now serves as the basis for C-C bond constructions that directly convert lower alcohols to higher alcohols. [16][17][18][19][20] This body of work was preceded by studies on metal catalyzed carbonyl reductive couplings mediated by elemental hydrogen, as initially described in 2002 by the present author, 27 and as documented in the review literature. 28,29 …”
mentioning
confidence: 90%
“…14,15 The purpose of this review is to provide a comprehensive summary of ruthenium catalyzed C-C couplings induced via alcohol-mediated transfer hydrogenation. [16][17][18][19][20] These studies build on several important milestones in the area of ruthenium catalyzed hydrogenation and transfer hydrogenation (Scheme 1). In 1971, one decade beyond the seminal work of Halpern on ruthenium catalyzed hydrogenation, 6 transfer hydrogenations employing ruthenium catalysts were described.…”
mentioning
confidence: 99%